Cardiac Monitoring in a Community Hospital—Analysis of 18 Months' Experience - Mc Henry, Malcolm M. (1968)
Cardiac monitoring facilities have been present in teaching hospital centers for over five years. A substantial decrease in mortality has been observed in monitored patients with acute myocardial infarction. The community hospital system offers a challenge to effective monitoring since many physicians care for patients and often many kinds of therapy are used. After 18 months of operation mortality from myocardial infarction was only 16.6 percent in a community hospital monitoring unit where the majority of the emergency care and resuscitation was carried out by nurses. Vital to this success was the use of standing orders for nurses, requirement of privilege to practice within the monitoring facility and acceptance of the nurse as a therapist in emergency situations. Fourteen patients were successfully resuscitated and were later discharged from the hospital. Four of them had ventricular fibrillation from digitalis intoxication. Patients with shock and severe congestive heart failure continue to be a major unsolved clinical problem. The results indicate that the potentially viable patient with serious electrical disturbances can almost invariably be salvaged.